Cluster management standards in Poland in the context of sustainable development - P. Kuraś (Global Journal of Environmental Science and Management)
The study relates to the problem of cluster management in the conditions of sustainable development. Against the background of the assumptions and conditions for sustainable development, the specificity of the cluster activity in the conditions of the Polish economy has been presented. The objective of the paper is to characterize the cluster management standards in Poland. Such standards have been formalized and published lately with the recommendation for their application by the Polish Agency for Enterprise Development. They constitute the response to the low level of the existing cluster management and lack of the system approach to the issue of the preparation of professional coordinators, whose significance is crucial for the cluster success. In the paper, the methods of literary study and the analysis of secondary data have been applied. The paper begins with the characteristics of the principles of sustainable development and their impact on cluster activity. It also indicates the role and significance of clusters in the contemporary economy. Subsequently, the author has conducted an analysis of cluster activities in Poland. The last part of the paper refers to the Polish standards for cluster management as well as the conclusions and recommendations.